2019
DOI: 10.1016/j.amjcard.2019.03.049
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Pattern of Growth Differentiation Factor-15 Protein After Acute Coronary Syndrome (From the BIOMArCS Study)

Abstract: for the BIOMArCS investigators Growth differentiation factor-15 (GDF-15) has appeared as a promising biomarker with strong predictive abilities in acute coronary syndrome (ACS). However, studies are solely based on single measurements in the acute phase of an ACS event. The way GDF-15 patterns in post-ACS patients behave on the long term is largely unknown. We conducted a nested case-control study within our multicenter, prospective, observational biomarker study (BIOMArCS) of 844 ACS patients. Following an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 13 publications
0
4
0
2
Order By: Relevance
“…Unlike troponin or BNP, acute myocardial injury induces only a modest increase of GDF-15 in the circulation (approximately 5% median increase), which occurs in the first week after an uncomplicated ACS event, and gradually returns back to baseline within 30 days. 32 , 33 This observation is supported by studies that suggest only a weak association between GDF-15 and extent of myocardial damage. 3 , 19 , 33 Similarly, HF studies have also reported low intraindividual and a higher interindividual biological variation with GDF-15.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Unlike troponin or BNP, acute myocardial injury induces only a modest increase of GDF-15 in the circulation (approximately 5% median increase), which occurs in the first week after an uncomplicated ACS event, and gradually returns back to baseline within 30 days. 32 , 33 This observation is supported by studies that suggest only a weak association between GDF-15 and extent of myocardial damage. 3 , 19 , 33 Similarly, HF studies have also reported low intraindividual and a higher interindividual biological variation with GDF-15.…”
Section: Discussionmentioning
confidence: 66%
“… 32 , 33 This observation is supported by studies that suggest only a weak association between GDF-15 and extent of myocardial damage. 3 , 19 , 33 Similarly, HF studies have also reported low intraindividual and a higher interindividual biological variation with GDF-15. 34 , 35 …”
Section: Discussionmentioning
confidence: 66%
“…Similar to the patients with stable CAD, GDF-15 levels are elevated in patients with ACS. In addition, there is also a significant association between high GDF-15 levels and mortality and recurrent MI in patients with ACS [28,29]. While a study suggested the use of GDF-15 in the early risk stratification of patients with acute chest pain [9], another study with a longer follow-up period reported that post-ACS patients who experience a recurrent event have stable and systematically higher GDF-15 levels during 30-days to 1-year follow-up compared to the event-free post-ACS patients [28].…”
Section: Discussionmentioning
confidence: 99%
“…GDF-15 has been found to be associated with recurrent events following ACS [28]. Further studies conducted by Nermina Buljubasic et al [29] demonstrated that the concentration of GDF-15 in patients with recurrent myocardial infarction after ACS was 26% higher than that in patients with non-recurrent ACS. Additionally, the concentration of GDF-15 in patients with recurrent events remained significantly higher than that in patients with non-recurrent ACS within 1 year.…”
Section: The Prognostic Value Of Gdf-15 In Acs Patientsmentioning
confidence: 97%